Osteological characterization of four putative species of the genus Adenomera (Anura: Leptodactylidae), with comments on intra- and interspecific variation - Ponssa, María Laura; Heyer, W. Ronald (Zootaxa, 2007)
Previous osteological characterizations of members of the frog genus Adenomera have been based on selected features. The purpose of this study is to establish a detailed osteological description of four putative species of the genus Adenomera. There is considerable variation, which we postulate corresponds to both intra- and interspecific variation. Osteology should provide a set of characters appropriate for cladistic analyses to help elucidate relationships within the Subfamily Leptodactylinae. Much of the adult osteological variation has a high probability of having evolved through the process of heterochrony.